Nutritional Status of Tetralogy of Fallot Patients at Dr. Hasan Sadikin General Hospital Bandung - Gabriella Cafrina; Armijn Firman; Gaga Irawan Nugraha (Althea Medical Journal, 2016)
Background: Undernutrition is common in children with congenital heart disease (CHD), especially in developing countries including Indonesia. The objective of the study was to describe the nutritional status of children patients with Tetralogy of Fallot.